The Influence of Family Environment, Peer Environment and Social Media on Consumptive Behavior with Religiosity as a Moderating Variable (Study on UIN Salatiga Students Scholarship Recipients) - Ratih Wulan Ndari; Imanda Firmantyas Putri Pertiwi (Social Science Studies, 2023)
Consumptive behavior is the behavior of consuming goods excessively just to meet the demands of lust. This study aims to determine the influence of Family Environment, Peer Environment and Social Media on the Consumptive Behavior of UIN Salatiga scholarship recipients, as well as to find out whether religiosity can moderate the influence of these three variables on consumptive behavior. This research is a quantitative study. The sample involved in this study was 222 UIN Salatiga students who received scholarships. Sample collection using purposive sampling technique. Data collection by spreading questionnaires digitally. The collected data were then analyzed with the Moderated Regression Analisys (MRA) test. From the results of the study, it is known that family environment and social media have no influence on consumptive behavior, while peer environtment has a positive and significant influence on consumptive behavior.